Patient involvement in blood transfusion safety: Patients' and healthcare professionals' perspective - Davis, R; Murphy, M; Sud, A; Noel, S; Moss, R; Asgheddi, M; Abdur-Rahman, I; Vincent, C (2012)
Background: Blood transfusion is one of the major areas where serious clinical consequences, even death, related to patient misidentification can occur. In the UK, healthcare professional compliance with pre-transfusion checking procedures which help to prevent misidentification errors is poor. Involving patients at a number of stages in the transfusion pathway could help prevent the occurrence of these incidents. Objectives: To investigate patients' willingness to be involved and healthcare professionals' willingness to support patient involvement in pre-transfusion checking behaviours. Measures: A cross-sectional design was employed assessing willingness to participate in pre-transfusion checking behaviours (patient survey) and willingness to support patient involvement (healthcare professional survey) on a scale of 1-7. Participants: One hundred and ten patients who had received a transfusion aged between 18 and 93 (60 male) and 123 healthcare professionals (doctors, nurses and midwives) involved in giving blood transfusions to patients. Results: Mean scores for patients' willingness to participate in safety-relevant transfusion behaviours and healthcare professionals' willingness to support patient involvement ranged from 4·96-6·27 to 4·53-6·66, respectively. Both groups perceived it most acceptable for patients to help prevent errors or omissions relating to their hospital identification wristband. Neither prior experience of receiving a blood transfusion nor professional role of healthcare staff had an effect on attitudes towards patient participation. Conclusion: Overall, both patients and healthcare professionals view patient involvement in transfusion-related behaviours quite favourably and appear in agreement regarding the behaviours patients should adopt an active role in. Further work is needed to determine the effectiveness of this approach to improve transfusion safety. © 2012 The Authors. Transfusion Medicine © 2012 British Blood Transfusion Society.